Cross-nativity marriages and human capital levels of children - Delia Furtado (Institute for the Study of Labor (IZA), 2009)
A common perception about immigrant assimilation is that association with natives necessarily speeds the process by which immigrants become indistinguishable from natives. Using 2000 Census data, this paper casts doubt on this presumption by examining the effect of an immigrant's marriage to a native, a measure of social integration, on dropout rates of children from these marriages. Although second-generation immigrants with one native parent generally have lower dropout rates than those with two foreign-born parents, the relationship reverses when steps are taken to control for observable and unobservable background characteristics. That is, immigrants that marry natives have children that are more likely to dropout of high school than immigrants that marry other immigrants. Moreover, gender differences in the effect of marriage to a native disappear in specifications which control for the endogeneity of the marriage decision.
Keywords: J12; J61; Z13; 330; Intermarriage; immigration; education; Migranten; Soziale Integration; Ehe; Humankapital; Bildungsabschluss; Kinder; Ethnische Gruppe; USA